2014
DOI: 10.1007/s11684-014-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of human umbilical cord mesenchymal stem cells for ischemic stroke: perspectives and challenges

Abstract: Ischemic stroke is a focal cerebral insult that often leads to many adverse neurological complications severely affecting the quality of life. The prevalence of stroke is increasing throughout the world, while the efficacy of current pharmacological therapies remains unclear. As a neuroregenerative therapy, the implantation of human umbilical cord mesenchymal stem cells (hUC-MSCs) has shown great possibility to restore function after stroke. This review article provides an update role of hUC-MSCs implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…MSC are multipotent adult progenitor cells, which can be isolated from various sources, such as bone marrow, placenta, umbilical cord, umbilical cord blood and adipose tissues ( 9 , 10 ). MSCs have the unique abilities of self-renewal, proliferation and multipotent differentiation, and can differentiate into the different cell types of the three germ layers; neurons, adipocytes, osteoblasts, hepatocytes, endothelial cells and islet b cells ( 11 13 ).…”
Section: Therapeutic Potential Of Mscs In the Treatment Of Strokementioning
confidence: 99%
See 1 more Smart Citation
“…MSC are multipotent adult progenitor cells, which can be isolated from various sources, such as bone marrow, placenta, umbilical cord, umbilical cord blood and adipose tissues ( 9 , 10 ). MSCs have the unique abilities of self-renewal, proliferation and multipotent differentiation, and can differentiate into the different cell types of the three germ layers; neurons, adipocytes, osteoblasts, hepatocytes, endothelial cells and islet b cells ( 11 13 ).…”
Section: Therapeutic Potential Of Mscs In the Treatment Of Strokementioning
confidence: 99%
“…A number of previous studies have confirmed the remarkable neuroregenerative ability of MSCs. MSC infusion in animal models of stroke have led to reduced infarct volume, enhanced synaptogenesis, increased vessel density and improved neurological function ( 9 ). In clinical trials, transplantation of MSCs was demonstrated to be a safe and feasible therapeutic strategy for stroke patients ( Table I ) ( 18 24 ).…”
Section: Therapeutic Potential Of Mscs In the Treatment Of Strokementioning
confidence: 99%
“…The last two decades have witnessed a surge in investigations proposing stem cells as a promising strategy to treat stroke ( Figure 1). Mesenchymal stem cells [6][7][8][9][10][11][12] from different sources including bone marrow [13,14] adipose tissue [15] and umbilical cord [16] as well as neural stem cells [17][18][19][20][21][22][23] are the most commonly used types of stem cells that have been employed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Modern regenerative medicine has demonstrated that transplantation of different kinds of stem cells can have a stimulating effect on the processes of reparative regeneration of the central and peripheral nervous system (Southwell et al, 2014;Li, Hu, and Cheng, 2015;Sokolova and Polyntsev, 2017). In recent years, experimental elaboration of different cellular technologies to stimulate regeneration of damaged nerves is being carried out intensively.…”
Section: Introductionmentioning
confidence: 99%